CARBONATE COMPLEXATION OF YTTRIUM AND THE RARE EARTH ELEMENTS IN NATURAL WATERS - Luo Y.R.; Byrne R.H. (My University, 2004)
Potentiometric measurements of Yttrium and Rare Earth Element (YREE) complexation by carbonate and bicarbonate indicate that the quality of carbonate complexation constants previously obtained via solvent exchange analyses are superior to characterizations obtained using solubility and adsorptive exchange analyses. The results of our analyses at 25°C are combined with the results of previous solvent exchange analyses to obtain YREE carbonate complexation constants over a wide range of ionic strength (0 ≤ I ≤3 molal). YREE carbonate complexation constants are reported for the following equilibria, M3++nHCO3−⇌M(CO3)n3−2n+nH+, where n = 1 or 2. Formation constants written in terms of HCO3− concentrations require only minor corrections for ion pairing relative to the corrections required for constants expressed in terms of CO32− concentrations. Formation constants for the above complexation equilibria, CO3Hβ1=[MCO3+][H+][M3+]−1[HCO3−]−1 and CO3Hβ2=[M(CO3)2−][H+]2[M3+]−1[HCO3−]−2, have very similar dependencies on ionic strength because the reaction MCO3++HCO3−⇌M(CO3)2−+H+ is isocoulombic. Potentiometric analyses indicate that the dependence of logCO3Hβ1 and logCO3Hβ2 on ionic strength at 25°C is given as (A)logCO3Hβn=logCO3Hβn0−4.088 I0.5/(1+3.033 I0.5)+0.042 I where CO3Hβn0 denotes a formation constant at 25°C and zero ionic strength. Recommended values for logCO3Hβ1 and logCO3Hβ20, expressed in the form (element, −logCO3Hβ10, −logCO3Hβ20), are as follows: (Y, 2.85, 8.03), (La, 3.60, 9.36), (Ce, 3.27, 8.90), (Pr, 3.10, 8.58), (Nd, 3.05, 8.49), (Sm, 2.87, 8.13), (Eu, 2.85, 8.03), (Gd, 2.94, 8.18), (Tb, 2.87, 7.88), (Dy, 2.77, 7.75), (Ho, 2.78, 7.66), (Er, 2.72, 7.54), (Tm, 2.65, 7.39), (Yb, 2.53, 7.36), (Lu, 2.58, 7.29).